Urgensi Pembelajaran Al-Qur'an Bagi Siswa Madrasah Ibtidaiyah - Fathor Rosi (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2021)
Given the importance of understanding the holy book of the Qur'an in educational institutions such as Madrasah Ibtida'iyah (MI), an effective learning method is needed, because it is known that there are still many phenomena of MI level students whose reading of the Qur'an is not good and many are from those who focus more on general subjects. Therefore, the purpose of writing this article is to describe a number of theoretical studies by taking references from books, journals, and other literature. As the results of the discussion of this article provide an overview and concept of the literature on how the Qur'anic learning model must be applied, namely; 1. The basic conception of learning the Qur'an; 2. Various methods of learning the Qur'an; 3. The importance of the Qur'anic learning method; 4. Development of relevant Qur'anic learning methods to be applied for MI students. Based on a number of theoretical discussions in this article, it is hoped that significant changes will occur for the improvement of MI students' knowledge in learning the Qur'an and for MI level education staff to apply the Qur'anic learning method for their students.